A method for enhancing chlorine evolution and efficiently mineralizing ammonia nitrogen using a metal electron-deficient configuration electric anode

By using metal-deficient electronic configuration electroanode material in the electrocatalytic system, Cl-enrichment and activation into Cl to generate free chlorine, the problems of low anode chlorine analysis performance and poor ammonia nitrogen oxidation removal performance in the prior art are solved. , achieving efficient and low-cost ammonia nitrogen mineralization effect.

CN115947422BActive Publication Date: 2025-02-25NANCHANG HANGKONG UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211715050.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-28
Publication Date
2025-02-25
Estimated Expiration
2042-12-28

AI Technical Summary

Technical Problem

In the existing electrocatalytic system, the anode chlorine analysis performance is low, the ammonia nitrogen oxidation removal performance is poor, and the cost is high. There are problems such as the chlorine analysis and oxygen evolution potentials close and the side reactions are serious.

Method used

The metal electron-deficient configuration electroanode material is used. By introducing elements with stronger electronegative properties than transition metals into the metal material, the configuration of the transition metal is adjusted. The platinum sheet electrode is used as the cathode, and a sodium chloride solution is used and a constant current is input. Induce Cl-enrichment and activation into ·Cl, generate free chlorine, broaden the difference in chlorine and oxygen evolution potentials, and efficiently mineralize ammonia nitrogen.

Benefits of technology

The binding capacity of the anode to Cl- is improved, the chlorine analysis performance and ammonia nitrogen removal performance are improved, and the cost is reduced, and the problems of low chlorine analysis performance and poor ammonia nitrogen oxidation removal performance in traditional electrocatalytic systems are overcome.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115947422B_ABST
    Figure CN115947422B_ABST
Patent Text Reader

Abstract

The invention discloses a method for enhancing the chlorine evolution and efficient mineralization of ammonia nitrogen by using a metal electron-deficient configuration electric anode. The method comprises the following steps: firstly, a metal material with a metal electron-deficient center is used as an electric anode material, an element with stronger electronegativity than the transition metal is introduced into the electric anode material, the configuration of the transition metal is adjusted, a platinum sheet electrode is used as a cathode, a sodium chloride solution is used as an electrolyte, and a constant current is input, so that the electric anode of the metal electron-deficient center can efficiently induce Cl ‑ The anode is enriched and the Cl ‑ The catalyst is activated to ·Cl, and then ·Cl is self-quenched and dissolved in water to generate free chlorine, which greatly broadens the potential difference between chlorine evolution and oxygen evolution, and efficiently and highly selectively mineralizes ammonia nitrogen in the solution into nitrogen gas. The present invention overcomes the problems of low anode chlorine evolution performance and poor ammonia nitrogen oxidation removal performance in traditional electrocatalytic systems, and has good feasibility and great potential for the treatment of actual wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sewage treatment, and in particular to a method for efficiently mineralizing ammonia nitrogen by strengthening chlorine evolution using a metal electron-deficient configuration electric anode. Background Art

[0002] Ammonia nitrogen, as an important chemical raw material, is widely used in industries such as chemical and electronics. The discharge of high-concentration ammonia nitrogen wastewater into natural water bodies will cause a series of environmental problems, such as eutrophication of water bodies, odor and complications of water supply disinfection. The national emission standard strictly stipulates that the emission concentration of ammonia nitrogen shall not exceed 5mg / L (level A), so the effective removal of ammonia nitrogen in wastewater has attracted widespread attention.

[0003] At present, the technologies widely used for ammonia removal include biological nitrification / denitrification, alkaline stripping, ion exchange, adsorption, chemical precipitation and breakpoint chlorination. However, these methods have the disadvantages of complex operation, poor treatment effect and high cost. Among them, breakpoint chlorination is the most commonly used method for treating ammonia nitrogen in industrial wastewater.

[0004] Add hypochlorite or introduce chlorine into the wastewater containing ammonia nitrogen, and use the strong oxidizing property of hypochlorous acid (1.49V) or hypochlorite (0.89V) to selectively oxidize ammonia nitrogen into nitrogen, as shown in formula (1) and (2). However, this method still has problems such as the difficulty in storing and transporting chlorine gas / hypochlorite, the large amount of chemical agents added, and the high cost.

[0005] In order to solve the above problems, the in-situ chlorine evolution reaction (CER) in the electrocatalytic system (EC) has been widely used to replace the traditional breakpoint chlorination method. Among them, the anode material is the most critical component in the electrocatalytic chlorine evolution reaction process. The commonly used electrode material with excellent chlorine evolution effect is the dimensionally stable anode (DSA), whose main component is iridium dioxide or ruthenium dioxide loaded on a titanium plate. In the electrochemical process, chloride ions can be effectively converted into chlorine gas at the anode, and then the chlorine gas dissolves in water to form active chlorine, as shown in formulas (3) to (5), and further oxidizes ammonia nitrogen to nitrogen. However, since the iridium oxide or ruthenium dioxide on the surface of DSA is a precious metal oxide, its cost is relatively high. In addition, in the electrochemical process of DSA, its chlorine evolution and oxygen evolution potentials are close, and the oxygen evolution side reaction is serious, resulting in poor chlorine evolution selectivity, which in turn affects the ammonia nitrogen removal performance. Therefore, it is necessary to develop a low-cost anode material with excellent chlorine evolution effect to replace the use of DSA.

[0006] 2NH4 + +3HClO→N2↑+3H2O+5H + +3Cl - (1)

[0007] 2NH4 + +4ClO -→N2↑+4H2O+2Cl - (2)

[0008] 2Cl - →Cl2+2e - (3)

[0009] Cl2+H2O→HClO+H + +Cl - (4)

[0010] Cl2+H2O→HClO+H + +Cl - (5)

[0011] Through in-depth analysis of the reaction mechanism of CER, it was found that Cl - First, it is enriched at the anode, and then activated to ·Cl through direct electron transfer on the electrode surface. Then ·Cl self-quenches to generate Cl2, as shown in equations (6) and (7). - The combination of Cl - The outer orbital electrons are in a saturated state. Under the action of the electric field, in addition to the electrostatic effect, the construction of an electron-deficient anode material can effectively promote the Cl - The combination of chlorine evolution and ammonia oxidation can be improved.

[0012] Cl - → Cl+e - (6)

[0013] ·Cl+·Cl→Cl2 (7)

[0014] Transition metal oxides have a large number of electron vacancies on their outer d orbitals, which can effectively promote the cycle of valence states. They are widely used as anodes in EC systems to replace the DSA electrodes of CER. However, due to their high chlorine evolution voltage and low selectivity, the CER performance of transition metal oxides is poor. Summary of the invention

[0015] The purpose of the present invention is to solve the technical problems existing in the prior art and provide a.

[0016] To achieve the above object, the technical solution provided by the present invention is: a method for enhancing the efficient mineralization of ammonia nitrogen by chlorine evolution by using a metal electron-deficient configuration electric anode, the method comprising the following steps: firstly, a metal material with a metal electron-deficient center is used as an electric anode material, an element with stronger electronegativity than the transition metal is introduced into the electric anode material, the configuration of the transition metal is adjusted, a platinum sheet electrode is used as a cathode, an electrolyte is a sodium chloride solution, and a constant current is input, so that the electric anode of the metal electron-deficient center can efficiently induce Cl -The anode is enriched and the Cl - After activation to ·Cl, ·Cl is self-quenched and dissolved in water to generate free chlorine, which broadens the potential difference between chlorine and oxygen evolution, and mineralizes ammonia nitrogen in the solution into nitrogen gas efficiently and selectively.

[0017] Furthermore, the current density of the constant current is 10-50 mA / cm 2 , electrolyte concentration is 10-70mmol, and reaction time is 1-2h.

[0018] Beneficial effects of the present invention:

[0019] The present invention overcomes the problems of low anode chlorine evolution performance and poor ammonia nitrogen oxidation removal performance in traditional electrocatalytic systems, and has good feasibility and huge potential for the treatment of actual wastewater. It also provides a new electrode design idea for subsequent application to other wastewaters. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings described herein are used to provide further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0021] Figure 1 The performance of different anodes in the electrocatalytic system for the degradation of ammonia nitrogen;

[0022] Figure 2 The concentration changes of ammonia and total nitrogen with Sb2O5-Co3O4 / Sn as anode;

[0023] Figure 3 XPS spectra of Co 2p orbitals before and after Co3O4 modification;

[0024] Figure 4 XPS spectra of Sb 3d and Sn 3d orbitals of Sb2O5-Co3O4, Co3O4 / Sn and Sb2O5-Co3O4 / Sn;

[0025] Figure 5 This is the quenching experiment of Sb2O5-Co3O4 / Sn in electrocatalytic reaction;

[0026] Figure 6 The concentration variation diagram of active chlorine in the anode reaction of Sb2O5-Co3O4 / Sn, Co3O4 and DSA;

[0027] Figure 7 For different anodes at a current density of 10 mA / cm 2 Chlorine evolution potential and oxygen evolution potential at

[0028] Figure 8The degradation of ammonia nitrogen in actual wastewater by Sb2O5-Co3O4 / Sn and DSA electrodes in the electrocatalytic system;

[0029] Fig. 9 The concentration change of total nitrogen in actual wastewater by Sb2O5-Co3O4 / Sn and DSA electrodes in the electrocatalytic system. DETAILED DESCRIPTION

[0030] This section will describe in detail the specific embodiments of the present invention. The preferred embodiments of the present invention are shown in the accompanying drawings. The purpose of the accompanying drawings is to supplement the description of the text part of the specification with graphics, so that people can intuitively and vividly understand each technical feature and the overall technical solution of the present invention, but it cannot be understood as a limitation on the scope of protection of the present invention.

[0031] In the description of the present invention, it should be understood that descriptions involving orientations, such as up, down, front, back, left, right, etc., and orientations or positional relationships indicated are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0032] In the description of the present invention, "several" means one or more, "more" means more than two, "greater than", "less than", "exceed" etc. are understood as not including the number itself, and "above", "below", "within" etc. are understood as including the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing the technical features, and cannot be understood as indicating or implying the relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0033] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention based on the specific content of the technical solution.

[0034] Reference Figure 1-Figure 9 The preferred embodiment of the present invention is a method for enhancing the efficient mineralization of ammonia nitrogen by chlorine evolution with a metal electron-deficient configuration electric anode. The method comprises the following steps: firstly, a metal material with a metal electron-deficient center is used as an electric anode material, an element with a stronger electronegativity than the transition metal is introduced into the electric anode material, the configuration of the transition metal is adjusted, a platinum sheet electrode is used as a cathode, the electrolyte is a sodium chloride solution, and a constant current is input, and the current density of the constant current is 10-50 mA / cm 2 , the electrolyte concentration is 10-70mmol, and the reaction time is 1-2h; thus, the metal electron-deficient center anode efficiently induces Cl - The anode is enriched and the Cl- After activation to ·Cl, ·Cl is self-quenched and dissolved in water to generate free chlorine, which broadens the potential difference between chlorine and oxygen evolution, and mineralizes ammonia nitrogen in the solution into nitrogen gas efficiently and selectively.

[0035] The electrocatalytic degradation of ammonia nitrogen in the present invention improves the selectivity of the electro-anodic chlorine evolution and the selectivity of the Cl - Subsequently, in the chlorine-mediated electrocatalytic system, the metal electron-deficient center anode efficiently induced Cl - The anode is enriched and the Cl - Activated to ·Cl. Subsequently, ·Cl self-quenches and dissolves in water to generate free chlorine (Cl2, HClO, ClO - ), efficiently and selectively mineralize ammonia nitrogen in the solution into nitrogen gas. The present invention overcomes the problems of low anode chlorine evolution performance and poor ammonia nitrogen oxidation removal performance in traditional electrocatalytic systems, and has good feasibility and great potential for the treatment of actual wastewater. At the same time, it provides a new electrode design idea for subsequent application to other wastewaters.

[0036] Embodiment 1 of the present invention

[0037] The electrocatalytic system of the present invention was constructed with Co electron-deficient center or DSA electrode as anode and platinum sheet as cathode, ammonia nitrogen wastewater as target pollutant, NaCl solution as electrolyte, and the current density was 10 mA / cm 2 The electrochemical reaction lasted for 2 hours, and samples were taken every 15 minutes during the reaction, and the product distribution in the samples was immediately determined. The catalytic degradation effect of the system on ammonia nitrogen was analyzed by analyzing the changes in the content of various products in the solution.

[0038] The specific preparation method of the electrode material in this embodiment is as follows:

[0039] Preparation method of anode Co3O4: First, ultrasonically clean the fluorine-doped tin oxide (FTO) substrate (1.5cm×4cm) with acetone, ethanol and ultrapure water for 15 minutes each, and dry it for use. Add 2mmol Co(NO3)2·6H2O to a mixture of ethylene glycol (10mL) and deionized water (30mL) in sequence. Then add urea (0.5g), hexadecyltrimethylammonium bromide (0.05g) and ammonium fluoride (1.455g) and stir for 30 minutes to form a uniform and transparent solution. Transfer the solution to a 100mL reactor and immerse the FTO substrate with the conductive surface facing up in the above solution. Keep the temperature at 120℃ for 12 hours. Then put the electrode into a muffle furnace and calcine it at 350℃ for 2 hours in an air atmosphere, and then calcine it at 550℃ for 2 hours.

[0040] Preparation method of anode Sb2O5-Co3O4: First, ultrasonically clean the FTO substrate (1.5cm×4cm) with acetone, ethanol and ultrapure water for 15 minutes each, and dry it for use. Co(NO3)2·6H2O and SbCl3 are added to a mixture of ethylene glycol (10mL) and deionized water (30mL) in a molar ratio of 20:1. Then urea (0.5g), hexadecyltrimethylammonium bromide (0.05g) and ammonium fluoride (1.455g) are added and stirred for 30 minutes to form a uniform and transparent solution. The solution is transferred to a 100mL reactor and a FTO substrate with the conductive surface facing up is immersed in the above solution. Keep the temperature at 120℃ for 12 hours. Then put the electrode into a muffle furnace and calcine at 350℃ for 2 hours in an air atmosphere, and then calcine at 550℃ for 2 hours.

[0041] Preparation method of anode Co3O4 / Sn: First, ultrasonically clean the FTO substrate (1.5cm×4cm) with acetone, ethanol and ultrapure water for 15 minutes each, and dry it for use. Co(NO3)2·6H2O and SnCl4·5H2O are added to a mixture of ethylene glycol (10mL) and deionized water (30mL) in a molar ratio of 20:1. Then urea (0.5g), hexadecyltrimethylammonium bromide (0.05g) and ammonium fluoride (1.455g) are added and stirred for 30 minutes to form a uniform and transparent solution. The solution is transferred to a 100mL reactor and a FTO substrate with the conductive surface facing up is immersed in the above solution. Keep the temperature at 120℃ for 12 hours. Then put the electrode into a muffle furnace and calcine at 350℃ for 2 hours in an air atmosphere, and then calcine at 550℃ for 2 hours.

[0042] Preparation method of anode Sb2O5-Co3O4 / Sn: First, ultrasonically clean FTO with acetone, ethanol and ultrapure water for 15 minutes each, and dry it for use. Co(NO3)2·6H2O, SbCl3 and SnCl4·5H2O are added to a mixture of ethylene glycol (10mL) and deionized water (30mL) in a molar ratio of 20:1:1. Then urea (0.5g), hexadecyltrimethylammonium bromide (0.05g) and ammonium fluoride (1.455g) are added and stirred for 30 minutes to form a uniform and transparent solution. The solution is transferred to a 100mL reactor and a FTO substrate with the conductive surface facing up is immersed in the above solution. Keep the temperature at 120℃ for 12 hours. Then put the electrode into a muffle furnace and calcine at 350℃ for 2 hours in an air atmosphere, and then calcine at 550℃ for 2 hours.

[0043] Embodiment 2 of the present invention

[0044] The electrocatalytic system of the present invention was constructed with Fe electron-deficient center or DSA electrode as anode and platinum sheet as cathode. The ammonia nitrogen in actual wastewater was used as the target pollutant and NaCl solution was used as electrolyte. The current density was 20 mA / cm 2 The electrochemical reaction lasted for 2 hours, and samples were taken every 15 minutes during the reaction, and the product distribution in the samples was immediately determined. The catalytic degradation effect of the system on ammonia nitrogen was analyzed by analyzing the changes in the content of various products in the solution.

[0045] The specific preparation method of the electrode material in this example is as follows:

[0046] Preparation method of anode Fe3O4: First, ultrasonically clean the FTO substrate (1.5cm×4cm) with hydrofluoric acid, acetone / ethanol and ultrapure water for 15 minutes each, and set aside after drying. Add 2mmol Fe(NO3)3·9H2O to a mixture of ethylene glycol (10mL) and deionized water (30mL) in sequence. Then add urea (0.5g), hexadecyltrimethylammonium bromide (0.05g) and ammonium fluoride (1.455g) and stir for 30 minutes to form a uniform and transparent solution. Transfer the solution to a 100mL reactor and immerse the FTO substrate with the conductive surface facing up in the above solution. Keep the temperature at 120℃ for 12 hours. Then put the electrode into a muffle furnace and calcine at 350℃ for 2 hours in an air atmosphere, and then calcine at 550℃ for 2 hours.

[0047] Preparation method of anode Sb2O5-Fe3O4: First, ultrasonically clean the FTO substrate (1.5cm×4cm) with hydrofluoric acid, acetone / ethanol and ultrapure water for 15 minutes each, and dry it for use. Add Fe(NO3)3·9H2O and SbCl3 in a molar ratio of 20:1 to a mixture of ethylene glycol (10mL) and deionized water (30mL) in sequence. Then add urea (0.5g), hexadecyltrimethylammonium bromide (0.05g) and ammonium fluoride (1.455g) and stir for 30 minutes to form a uniform and transparent solution. Transfer the solution to a 100mL reactor and immerse a FTO substrate with the conductive surface facing up in the above solution. Keep the temperature at 120℃ for 12 hours. Then put the electrode into a muffle furnace and calcine it at 350℃ for 2 hours in an air atmosphere, and then calcine it at 550℃ for 2 hours.

[0048] Preparation method of Fe3O4 / Sn anode: First, ultrasonically clean the FTO substrate (1.5cm×4cm) with hydrofluoric acid, acetone / ethanol and ultrapure water for 15 minutes each, and dry it for use. Fe(NO3)3·9H2O and SnCl4·5H2O were added to a mixture of ethylene glycol (10mL) and deionized water (30mL) in a molar ratio of 20:1. Then urea (0.5g), hexadecyltrimethylammonium bromide (0.05g) and ammonium fluoride (1.455g) were added and stirred for 30 minutes to form a uniform and transparent solution. The solution was transferred to a 100mL reactor and a FTO substrate with the conductive surface facing up was immersed in the above solution. Keep the temperature at 120℃ for 12 hours. Then the electrode was placed in a muffle furnace and calcined at 350℃ for 2 hours in an air atmosphere, and then calcined at 550℃ for 2 hours.

[0049] Preparation method of anode Sb2O5-Fe3O4 / Sn: First, ultrasonically clean FTO with hydrofluoric acid, acetone / ethanol and ultrapure water for 15 minutes each, and dry it for use. Fe(NO3)3·9H2O, SbCl3 and SnCl4·5H2O were added to a mixture of ethylene glycol (10mL) and deionized water (30mL) in a molar ratio of 20:1:1. Then urea (0.5g), hexadecyltrimethylammonium bromide (0.05g) and ammonium fluoride (1.455g) were added and stirred for 30 minutes to form a uniform and transparent solution. The solution was transferred to a 100mL reactor and a FTO substrate with the conductive surface facing up was immersed in the above solution. The temperature was kept at 120℃ for 12 hours. Then the electrode was placed in a muffle furnace and calcined at 350℃ for 2 hours in an air atmosphere, and then calcined at 550℃ for 2 hours.

[0050] Embodiment 3 of the present invention

[0051] The electrocatalytic system of the present invention was constructed with Ni electron-deficient center or DSA electrode as anode and platinum sheet as cathode. The ammonia nitrogen in actual wastewater was used as the target pollutant and NaCl solution was used as electrolyte. The current density was 10 mA / cm 2 The electrochemical reaction lasted for 2 hours, and samples were taken every 15 minutes during the reaction, and the product distribution in the samples was immediately determined. The catalytic degradation effect of the system on ammonia nitrogen was analyzed by analyzing the changes in the content of various products in the solution.

[0052] The specific preparation method of the electrode material in this example is as follows:.

[0053] Preparation method of anode NiO: First, ultrasonically clean the fluorine-doped tin oxide (FTO) substrate (1.5cm×4cm) with acetone, ethanol and ultrapure water for 15 minutes each, and dry it for use. Add 2mmol Ni(NO3)2·6H2O to a mixture of ethylene glycol (10mL) and deionized water (30mL) in sequence. Then add urea (0.5g), hexadecyltrimethylammonium bromide (0.05g) and ammonium fluoride (1.455g) and stir for 30 minutes to form a uniform and transparent solution. Transfer the solution to a 100mL reactor and immerse the FTO substrate with the conductive surface facing up in the above solution. Keep the temperature at 120℃ for 12 hours. Then put the electrode into a muffle furnace and calcine it at 350℃ for 2 hours in an air atmosphere, and then calcine it at 550℃ for 2 hours.

[0054] Preparation method of anode Sb2O5-NiO: First, ultrasonically clean the FTO substrate (1.5cm×4cm) with acetone, ethanol and ultrapure water for 15 minutes each, and dry it for use. Ni(NO3)2·6H2O and SbCl3 are added to a mixture of ethylene glycol (10mL) and deionized water (30mL) in a molar ratio of 20:1. Then urea (0.5g), hexadecyltrimethylammonium bromide (0.05g) and ammonium fluoride (1.455g) are added and stirred for 30 minutes to form a uniform and transparent solution. The solution is transferred to a 100mL reactor and a FTO substrate with the conductive surface facing up is immersed in the above solution. Keep the temperature at 120℃ for 12 hours. Then put the electrode into a muffle furnace and calcine at 350℃ for 2 hours in an air atmosphere, and then calcine at 550℃ for 2 hours.

[0055] Preparation method of anode NiO / Sn: First, ultrasonically clean the FTO substrate (1.5cm×4cm) with acetone, ethanol and ultrapure water for 15 minutes each, and dry it for use. Ni(NO3)2·6H2O and SnCl4·5H2O are added to a mixture of ethylene glycol (10mL) and deionized water (30mL) in a molar ratio of 20:1. Then urea (0.5g), hexadecyltrimethylammonium bromide (0.05g) and ammonium fluoride (1.455g) are added and stirred for 30 minutes to form a uniform and transparent solution. The solution is transferred to a 100mL reactor and a FTO substrate with the conductive surface facing up is immersed in the above solution. Keep the temperature at 120℃ for 12 hours. Then the electrode is placed in a muffle furnace and calcined at 350℃ for 2 hours in an air atmosphere, and then calcined at 550℃ for 2 hours.

[0056] Preparation method of anode Sb2O5-NiO / Sn: First, ultrasonically clean FTO with acetone, ethanol and ultrapure water for 15 minutes each, and dry it for use. Ni(NO3)2·6H2O, SbCl3 and SnCl4·5H2O are added to a mixture of ethylene glycol (10mL) and deionized water (30mL) in a molar ratio of 20:1:1. Then urea (0.5g), hexadecyltrimethylammonium bromide (0.05g) and ammonium fluoride (1.455g) are added and stirred for 30 minutes to form a uniform and transparent solution. The solution is transferred to a 100mL reactor and a FTO substrate with the conductive surface facing up is immersed in the above solution. Keep the temperature at 120℃ for 12 hours. Then the electrode is placed in a muffle furnace and calcined at 350℃ for 2 hours in an air atmosphere, and then calcined at 550℃ for 2 hours.

[0057] The complete mineralization of ammonia nitrogen and its mechanism of action of the present invention are discussed in detail through the specific experimental results of Example 1 of the present invention.

[0058] like Figure 1-4 As shown in the figure, after 90 minutes of electrocatalytic reaction, the ammonia nitrogen removal rates were 89% and 62% when Co3O4 and DSA were used as anodes, respectively. In contrast, after the introduction of Sb and Sn alone, the ammonia nitrogen removal performance in the EC system of Sb2O5 / Co3O4 and Co3O4 / Sn anodes was 92% and 79%, respectively. Sn was introduced alone into Co3O4, because Sn replaced Co in Co3O4. 2+ , slightly inhibiting Co 2+ / Co 3+ cycle, thereby inhibiting the CER performance of the anode. In the EC system with Sb2O5-Co3O4 / Sn as the anode, the removal rate of ammonia nitrogen can reach 100%. Therefore, the simultaneous introduction of Sb and Sn into Co3O4 promotes the efficient removal of ammonia nitrogen, indicating that a synergistic effect will occur between Sb and Sn, which will increase the CER activity of Co3O4 and promote the removal of ammonia. In addition, the total nitrogen concentration decreases synchronously with the decrease of ammonia nitrogen concentration, indicating that ammonia nitrogen can be efficiently and selectively oxidized to N2 rather than nitrate or nitrite in this electrocatalytic system. These results show that the Sb2O5-Co3O4 / Sn electrode has better deammonification performance than Co3O4 and DSA electrodes.

[0059] At the same time, XPS tests were performed on the materials before and after doping. 3 / 2 and Co2p 1 / 2 The binding energy of the orbitals remains unchanged, indicating that there is no electron shift between Co and Sn. When Sb is introduced into Co3O4, Co 2p 3 / 2 , Co 2p 1 / 2The binding energy of the orbital shifts toward the low energy direction, indicating that the electron cloud around Co in Co3O4 moves toward Sb, thereby inducing the formation of electron-deficient Co active sites of CER. When Sn is introduced into Sb2O5-Co3O4, the binding energy of Co 2p3 / 2 and Co 2p1 / 2 further shifts toward the low energy direction, indicating that the electron deficiency of Co in Sb2O5-Co3O4 / Sn is stronger than that in Sb2O5-Co3O4. Compared with Sb2O5-Co3O4 and Co3O4 / Sn, the binding energy of Sb 3d orbital in Sb2O5-Co3O4 / Sn decreases, while the binding energy of Sn 3d orbital increases. This result shows that the introduction of Sb and Sn into Co3O4 causes the electron cloud around Co to move toward Sb, and the electron cloud around Sb to move toward Sn, and the electrons of Co will be further reduced. In summary, the simultaneous introduction of Sb and Sn into Co3O4 constructs a strongly electron-deficient Co active site, which is beneficial to Cl - The enrichment of Sb2O5-Co3O4 / Sn further improves the CER activity and selectivity of Sb2O5-Co3O4 / Sn anode.

[0060] like Figure 5-7 In order to explore the effect of free radical species on ammonia nitrogen removal in the Sb2O5-Co3O4 / Sn electrocatalytic reaction, a free radical quenching experiment was carried out. The degradation effect of ammonia nitrogen was almost not inhibited after the addition of tert-butyl alcohol (TBA), indicating that hydroxyl radicals, chlorine radicals and chlorine oxide radicals did not contribute to the removal of ammonia nitrogen during the Sb2O5-Co3O4 / Sn electrocatalytic reaction. Subsequently, the concentration change of free chlorine was studied. Due to the continuous consumption of free chlorine by ammonia nitrogen, the free chlorine concentration was much lower than 1 mg / L within 90 minutes. After the ammonia nitrogen was completely removed, free chlorine was no longer consumed, and its concentration increased significantly. Therefore, the dominant species for ammonia nitrogen removal in this electrocatalytic system is free chlorine.

[0061] By measuring the CER activity and selectivity of the electrode, the catalytic effect of the electron-deficient configuration anode in the electrocatalytic system for the removal of ammonia nitrogen was further explored. The chlorine evolution reaction and oxygen evolution reaction potentials of the Sb2O5-Co3O4 / Sn anode were 1.17 and 1.57 V, respectively. In comparison, the chlorine evolution reaction and oxygen evolution reaction potentials of the Co3O4 anode were 1.25 and 1.60 V, respectively. The Sb2O5-Co3O4 / Sn anode has higher CER activity and selectivity than the Co3O4 anode due to its lower chlorine evolution potential and larger potential difference between chlorine evolution and oxygen evolution. Although the DSA electrode has strong CER kinetics, the close chlorine evolution potential (1.10 V) and oxygen evolution potential (1.16 V) can cause severe oxygen evolution side reactions, inhibiting the CER selectivity of the DSA electrode. In summary, the introduction of Sb and Sn in Co3O4 can effectively expand the potential difference between OER and CER, thereby improving the activity and selectivity of the anode CER, and thus achieving efficient removal of ammonia nitrogen.

[0062] like Figure 8-9 As shown, when Sb2O5-Co3O4 / Sn was used as the anode to treat actual ammonia nitrogen wastewater, the ammonia concentration dropped from 135 mg-N / L to 22 mg-N / L within 12 hours, and the ammonia removal rate was 83.7%, which was much better than the 62.2% of the DSA anode. In addition, the reduction in total nitrogen concentration was close to the reduction in ammonia nitrogen concentration, indicating that ammonia nitrogen can be effectively mineralized into N2 in the electrocatalytic system.

[0063] It can be seen from the above examples that the present invention designs a new anode material with a metal electron-deficient configuration having high CER performance, which greatly broadens the potential difference between the chlorine evolution potential and the oxygen evolution potential, and improves the electrode's Cl - Therefore, the metal electron-deficient central anode has high selectivity and activity for CER, and has a good ammonia nitrogen mineralization effect, and its performance is far better than that of commercial DSA electrodes. In addition, this strategy is feasible to achieve effective mineralization of wastewater in practical applications. Therefore, the present invention provides a new design idea for the construction of efficient chlorine evolution electrode materials.

[0064] Under the premise that no conflict occurs, those skilled in the art may freely combine and superimpose the above-mentioned additional technical features.

[0065] The above description is only a preferred implementation mode of the present invention. Any technical solution that achieves the purpose of the present invention by substantially the same means belongs to the protection scope of the present invention.

Claims

1. A method for enhancing the efficient mineralization of ammonia nitrogen by chlorine evolution using a metal electron-deficient configuration electric anode, characterized in that: The method comprises the following steps: firstly, a transition metal oxide such as Co3O4, Fe3O4 or NiO and a metal material with electron-deficient center are used as an electric anode material, elements Sn and Sb with stronger electronegativity than the transition metal are introduced into the electric anode material, the configuration of the transition metal is adjusted, a platinum sheet electrode is used as a cathode, a sodium chloride solution is used as an electrolyte, and a constant current is input, so that the electric anode of the metal electron-deficient center can efficiently induce Cl - The anode is enriched and the Cl - After activation to •Cl, •Cl is self-quenched and dissolved in water to generate free chlorine, which broadens the potential difference between chlorine and oxygen evolution, and mineralizes ammonia nitrogen in the solution into nitrogen gas efficiently and selectively.

2. The method for enhancing the efficient mineralization of ammonia nitrogen by chlorine evolution using a metal electron-deficient configuration electric anode according to claim 1, characterized in that: The current density of the constant current is 10 - 50 mA / cm 2 , electrolyte concentration is 10 – 70 mmol, and reaction time is 1 – 2 h.

Citation Information

Patent Citations

  • Ammonia-nitrogen wastewater degradation system and method for generating oxychloride radical based on photoelectrocatalysis

    CN110078195A

  • Method for removing ammonia nitrogen in water through TiO2-NTs / Sb-SnO2 / PbO2 electrocatalytic oxidation and application of method

    CN113511763A